2022
DOI: 10.1038/s41598-022-16992-9
|View full text |Cite
|
Sign up to set email alerts
|

Midguts of Culex pipiens L. (Diptera: Culicidae) as a potential source of raw milk contamination with pathogens

Abstract: Despite their importance, only few studies focused on the mosquitoes borne microbial diseases, especially bacterial and fungal diseases, their vectorial capacity toward microorganisms, and their important role in raw milk contamination with pathogens in some unsanitary dairy farms. In Egypt, where Culex pipiens is the historical main vector of lymphatic filariasis, only few studies discussed the isolation of pathogens from the midguts of different stages of C. pipiens. This study aims to isolate and identify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The previous investigations on Culex species microbiota were run by conventional bacterial culture, PCR 16S rRNA, and DNA sequencing for the detection of various bacterial strains ( 40 , 41 ) and continued by up-to-date approaches: RNA shotgun metagenomic sequencing, next generation sequencing, culturomics, and MALDI-TOF MS ( 24 , 42 44 ). Next-generation sequencing method revealed the presence of Wolbachia, Streptococcus, Stenotrophomonas, Staphylococcus, Corynebacterium, and Rothia in ovaries of female Cx.…”
Section: Discussionmentioning
confidence: 99%
“…The previous investigations on Culex species microbiota were run by conventional bacterial culture, PCR 16S rRNA, and DNA sequencing for the detection of various bacterial strains ( 40 , 41 ) and continued by up-to-date approaches: RNA shotgun metagenomic sequencing, next generation sequencing, culturomics, and MALDI-TOF MS ( 24 , 42 44 ). Next-generation sequencing method revealed the presence of Wolbachia, Streptococcus, Stenotrophomonas, Staphylococcus, Corynebacterium, and Rothia in ovaries of female Cx.…”
Section: Discussionmentioning
confidence: 99%
“…It is essential to consider that microbial contamination from the dairy environment also includes residues of milk, from either healthy or diseased cows, that could persist in the environment due to poor sanitation and hygiene dairy practices. Milk residue on utensils and milking equipment represent feeding elements for flies ( 47 ). Once fed and when flies find another food source or place to lay eggs, the crop fluids are either externally released by regurgitation or ingested internally to the gut to be then re-emitted into the environment by defecation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the leaves, fruits, and barks of Z. spina-christi have reported that these plant parts exhibit hypoglycemic, antihyperglycemic ( Abdel-Zaheret al, 2005 , Glombitzaet al, 1994 , Nesseemet al, 2009 ), antidiabetic ( Takım, 2021 ), antidiarrheal ( Adlyet al, 2022 , Adzuet al, 2003 , Neamahet al, 2022 ), antibacterial ( El Kutry and Sopeah, 2020 ), antinociceptive ( Adzuet al, 2001 , Dhanalekshmiet al, 2022 ), analgesic, antihyperlipidemic, and antioxidant effects ( Adzu and Haruna, 2010 , Alsayari and Wahab, 2021 , Dkhilet al, 2018 , Husseinet al, 2006 ). In addition, the ethanolic extract of the leaves of this species has been reported to inhibit the growth of Bacillus subtilis and exert moderate antipyretic and considerable anti-inflammatory activities ( Tanira et al, 1988 ).…”
Section: Introductionmentioning
confidence: 99%